Sheet paper attracting system - NISHIBORI; TOSHIKI (1986)
A paper sheet attracting system includes a suction air casing and a paper sheet attracting unit which has a bottom wall provided with a plurality of air intake openings. The paper sheet attracting unit is slidably connected to the suction air casing via a flexible duct, and the paper sheet attracting unit is normally pulled downward so that the bottom wall contacts the uppermost paper sheet supported by a paper sheet holder. When the height of the uppermost paper sheet varies, the flexible duct allows the shifting of the paper sheet attracting unit so that the bottom wall of the paper sheet attracting unit contacts the uppermost paper sheet.